PENGEMBANGAN SISTEM EVALUASI DOSEN MENGGUNAKAN LOGIKA FUZZY - Chrisantus Tristianto (Institut Sains dan Teknologi Nasional, 2022)
Abstract In educational institutions, success is measured by the achievements of lecturers, or how many qualified lecturers meet the competency standards set by the Higher Education policy or campus quality assurance institution. This study tends to examine the superiority of the membership function in the process for fuzzy inference using the Mamdani method, to further accelerate and sharpen the accuracy of the lecturer's assessment by applying scientific techniques and also to avoid errors in the assessment that can be done manually. The results of our method for several real samples show that our approach can be used to evaluate the performance of Information Systems lecturers at Pamulang University. Keywords: Fuzzy logic, Lecturer Evaluation, Matlab, Mandani